Determination of Cikapundung River Water Quality Index Using IKA-INA Method and Pollution Index - Tati Artiningrum; Nadia Syarah Saeful (Eduvest - Journal of Universal Studies, 2023)
The Cikapundung River which crosses the city of Bandung is widely used for various purposes including as a drainage, tourist attraction and raw material for drinking water. In fact, the Cikapundung River is inseparable from environmental pollution, both from domestic waste around the river flow and industrial waste which ultimately has an impact on decreasing water quality. This research aims to to get an overview of the water quality condi-tions of the Cikapundung river which were assessed using Index IKA-INA method. To see how big the impact is on water quality in the Cikapundung River, a water quality index is used, which is a method for assessing the condition of a body of water based on selected parameters. Sampling was carried out at 3 sites during the dry and rainy seasons. Then the water quality criteria are determined using the National Sanitation's Foundation (NSF-WQI) method which has been modified to become the IKA-INA method and Pollution Index (IP) based on Minister of Environment Regulation No. 115 of 2003 concerning guidelines for determining water quality status. The results of the analysis using the IKA-INA method, the water quality of the Cikapundung River is generally in the "moderate" category, only one site is included in the "good enough" category, while the determination of water quality status using the Pollution Index method is included in the "fair" category. Moderately Polluted” for all sites both during the dry and rainy seasons with IP values ​​ranging from 1.36 to 4.38.